2005
DOI: 10.1037/h0088896
|View full text |Cite
|
Sign up to set email alerts
|

School-Based Child-Centered Play Therapy with Hispanic Children: Outcomes and Cultural Consideration.

Abstract: Hispanic children are the fastest growing segment of the population. Numerous factors place them at-risk for school success. This study examined the effects of Child-Centered Play Therapy (CCPT) compared to a curriculum-based small group intervention with 29 Hispanic children referred for school counseling due to behavior problems. Children were assigned to treatment groups by random drawing within grade levels. Treatment was provided by Hispanic bilingual counselors. Statistical analysis revealed that, accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
81
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 27 publications
13
81
0
1
Order By: Relevance
“…Similarly, the results of the study by Baggerly (2004) showed that child-centered play therapy increases children's selfesteem. In addition, the results of this research are in line with studies that indicate play therapy to be influential in reducing the behavioral problems among children [20,21,33] and studies that show group play therapy improves children's social skills [15], as well as with studies revealing play therapy to increase children's self-esteem [16].…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, the results of the study by Baggerly (2004) showed that child-centered play therapy increases children's selfesteem. In addition, the results of this research are in line with studies that indicate play therapy to be influential in reducing the behavioral problems among children [20,21,33] and studies that show group play therapy improves children's social skills [15], as well as with studies revealing play therapy to increase children's self-esteem [16].…”
Section: Discussionsupporting
confidence: 74%
“…For both LT and ST conditions, teachers noted a drop in their stress level related to student problems, which resulted in a significant decrease in total teacher-child relationship stress. Previous studies in play therapy have revealed that it can have a beneficial effect on children with general behavioral problems (Raman & Kapur, 1999;Shashi, Kapur, & Subbakrishna, 1999), externalizing behavioral problems (Flahive, 2005;Garza & Bratton, 2005;Kot, Landreth, & Giordano, 1998), and internalizing problems (Packman & Bratton, 2003). It seems likely that interventions (such as CCPT), designed to reduce childhood behavioral problems, would result in a reduction in overall relationship stress.…”
Section: Effect On Student/teacher Characteristicsmentioning
confidence: 93%
“…Garza and Bratton (2005) specifically examined CCPT with Hispanic students at the elementary level and found that students in the CCPT group had significant decreases in parent-reported externalizing behavioral problems as compared to a curriculum-based small group intervention. In conducting CCPT with children identified with aggressive behaviors, Schumann (2005) found that CCPT was as effective as an evidence-based guidance curriculum in reducing aggressive behaviors in students.…”
Section: Ccpt In the Schoolsmentioning
confidence: 98%
“…The majority of play therapy studies explore the effectiveness of play therapy in a once-aweek format (Baggerly & Jenkins, 2009;Fall, Navelski, & Welch, 2002;Garza & Bratton, 2005;Schumann, 2010). In these studies, play therapy is delivered to children one time a week for 45 minutes.…”
Section: Ccpt Session Structurementioning
confidence: 99%
“…Results demonstrated that children assigned to CCPT intervention demonstrated statistically significant decreases in aggressive behaviors and the control group made little improvement. Garza and Bratton (2005) investigated effects of twice-weekly CCPT on elementary aged Hispanic children exhibiting externalized behavioral problems compared to an active curriculum-based control group with the same twice-weekly schedule. The results indicated that children who received CCPT sessions demonstrated statistically significant decreases in externalizing behaviors problems compared to the active control group.…”
Section: Externalizing Behaviors and Ccptmentioning
confidence: 99%